PENATAAN KEMBALI KORIDOR KOMERSIAL JALAN GAJAH MADA KOTA PONTIANAK - Meilinda, Dewi
Street corridor is a linear shaped public facility that is placed between buildings and streets. Corridor's arrangement used to create a better interaction space for the public. Commercial street corridor is a type of city's corridor located in commercial areas which mostly offer a variety of services. On the other hand, corridor's functionality has shifted and often misused as private interests. In this research, corridor's re - arrangement will be conducted at Gajah Mada Street, Pontianak because it offers wide variations of services but without a proper corridor which decreases the public safety. The answer to this problem is to conduct a research with the fragmental method approach with data collection in the form of secondary data (literature review) and primary data (observation) to arrange Gajah Mada street's corridor to increase its safety and enjoyment. In this research, literature review will be used as the base normative arrangement with placemaking concept, location review to gather the potentials and problems, and to design the corridor of Gajah Mada street based on the defined normative arrangement and existing arrangement. This research concludes that placemaking concept can be applied to the location. The researched location also held its potential as a place for the society to interact as the existing problems can be solved by providing corridors with parking place for vehicles, pedestrian streets equipped with street facilities, a place which clearly distinguish between street merchants, pedestrian streets, and on-street parking